PENGARUH PEMBERIAN BORON DAN WAKTU PEMANENAN POLEN TERHADAP PENINGKATAN PRODUKSI DAN VIABILITAS POLEN TETUA JANTAN SEMANGKA (Citrullus lanatus Thunberg.) - Aris Susanto; Sri Hartatik; Muh. Burhan Rosyidi (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
Pollen management is one of the important factors in the production of hybrid seeds. The main obstacle in the seed production of hybrid watermelon are the appearance of the flowers do not coincide, and limited the availability of pollen with high viability. This research aims to the of dosage of boron and pollen harvesting time the pollen production and viability of pollen watermelon male parent. The research was done on a farm Seed Production Research Land of PT. Benih Citra Asia, sub-district Ajung, districts Jember and done with a random group of factorial design of experiments, with the first factor: 4 level doses of boron, and the second factor: 3 time harvesting the pollen, with each combination treatment is repeated as many as three times. The research result of which demonstrate of application of boron 1,0 kg ha-1 and time of harvesting the pollen pre-anthesis produces the successs of pollination to 100%. The boron dosage 1 kg ha-1 is able to give the age of male flowers faster which is 25,89 DAP, and the age of female flowers is faster which is 31,67 DAP, and produces a higher fruit set that is 94,44%. The time for harvesting pollen in anthesis phase produces the highest pollen germination, which 63,81%.Keywords: male flower, media Brewbaker and Kwack, germination pollen, fruit set